Analisis Pragmatik Shikkari dalam Tuturan Bahasa Jepang - Fizati Nara Prameswari; Yuniarsih Yuniarsih; Ruri Fadhillah Hakim (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2025)
This study examines the function of shikkari in illocutionary speech acts in Japanese utterances on the social media platform X. The research aims to uncover the pragmatic functions of shikkari through the framework of illocutionary acts and Searle’s constitutive rules (1979). A qualitative method was employed, with data collected from posts between January and August 2025. The analysis focused on grammatical structure to determine whether shikkari functions as an adverb or verb, based on Kamiya (2002) and Terada (in Sudjianto & Dahidi, 2007), and its lexical meaning as explained by Kindaichi (1997). Searle’s constitutive rules were then applied to classify the types of illocutionary acts. A total of 56 utterances were analyzed, resulting in four categories: assertive (14), directive (19), expressive (18), and commissive (5), while declaratives were absent due to the lack of formal institutional contexts. The findings indicate that shikkari functions not only as an adverb but also as a verb when combined with suru (e.g., shikkari shiteiru, shikkari shiro, shikkari shiyou). Pragmatically, three main tendencies emerge: (1) when referring to a person, shikkari means “reliable” or “having the potential to become a great person,” comparable to tanomoshii; (2) in imperative forms such as shikkari shiro directed to institutions, it conveys “wise and responsible” or “resilient under pressure,” comparable to kenjitsu and kizen; (3) when referring to objects, shikkari signifies “precise and detailed,” comparable to seimitsu. In conclusion, the study highlights the contextual and multifaceted nature of shikkari. These findings contribute to research on Japanese adverbs and provide valuable insights for learners, translators, and scholars.